EFFECT OF SPECIES AND SEASON ON LAMINITIS PREVALENCE IN SEMEN-DONOR BULLS - Prihatin, Koko Wisnu; Jumaryoto, Jumaryoto; Indarjulianto, Soedarmano (Universitas Syiah Kuala, 2022)
The objective of this study is to determine the effect of species, season, and their interaction on laminitis prevalence in three semen-donor bull species in the Artificial Insemination Centre under tropical conditions. The average prevalence in each species (Bos taurus, Bos indicus, and Bos sondaicus) was calculated based on the number of monthly incidents compared to the current population during 2020, while the two-way ANOVA was used to determine the effect of species, seasons (wet and dry season) and species-season interactions to the prevalence of laminitis. The average prevalence in Bos taurus, indicus, and sondaicus during dry season was 7.5821.841%, 1.1901.844%, 0.4511.103%, and during wet season was 8.5214.808%, 1.2621.960%, 0.4511.103% respectively. This study revealed that Bos taurus bull species more susceptible to laminitis compared to Bos indicus and Bos sondaicus. However, there is no influence of seasons and interactions between seasons and species on laminitis prevalence. In conclusion, this study has proven that laminitis can occur in all semen-donor bull species despite differences in susceptibility, species, or season.